Effect of the Addition of Dried Dandelion Roots (Taraxacum officinale F. H. Wigg.) on Wheat Dough and Bread Properties - Grażyna Cacak-Pietrzak; Dariusz Dziki; Urszula Gawlik-Dziki; Alicja Sułek; Stanisław Kalisz; Katarzyna Sujka (Molecules, 2021)
Dried and crushed dandelion roots (Taraxacum officinale F. H. Wigg.) (TO) were used as a formulation additive (at the amount of 0, 1, 3, 4, 5, and 6 g 100 g−1 flour) to wheat bread. The farinographic properties of the dough and the physical and chemical properties of the bread were evaluated. It was found that the addition of dried flour caused a significant decrease in water absorption by the flour (1% and higher TO level), an increase in the development time (from 2% to 5% TO addition) and dough stability (3% and 4% TO level), and an increase in dough softening (4% and higher TO level). As the substitution of TO for wheat flour increased, there was a gradual decrease in loaf volume, an increase in specific weight and crumb hardness, and a darkening of the crumb color. The total polyphenol content increased linearly with the percentage increase of dried root additions TO from 0.290 to 0.394 mg GAE g−1 d.m., which translated into an increase in the antioxidant activity of the bread. It was found that dried crushed roots of Taraxacum officinale can be a recipe additive for wheat bread; however, due to their specific smell and bitter aftertaste, the level of this additive should not exceed 3 g 100 g−1 flour.